Rapid Fabrication of an Inverse Opal TiO2 Photoelectrode for DSSC Using a Binary Mixture of TiO2 Nanoparticles and Polymer Microspheres - Seo, Young Gon; Woo, Kyoungja; Kim, Junkyung; Lee, Hyunjung; Lee, Wonmok (WILEY-BLACKWELL, 2011)
A rapid fabrication method of highly reflective TiO2 inverse opal (IO) film exhibiting controllable thickness, high TiO2 content, and excellent interfacial contact with glass substrate is presented. By inducing accelerated solvent evaporation during the colloidal self-assembly process, a composite film of polystyrene (PS)/TiO2 has been directly fabricated on a fluorine doped tin oxide (FTO) glass substrate, which exhibits the highly ordered opaline structure of PS embedded into the TiO2 matrix. This hybrid fabrication path leads to the formation of layers with the preferred {111} face-centered cubic (FCC) orientation parallel to the substrate and to produce a 1 cm(2)-wide well-ordered composite colloidal crystal film in less than 30 min. The film showed highly ordered FCC structure, particularly at the upper region, due to the induced solvent evaporation and exhibited a reliable light modulation at a reflectance mode. Regardless of the size of sacrificial PS microspheres, TiO2 IO films of controllable thickness were successfully formed by varying the moving speed of the fabrication cell. The binary aqueous dispersion of tailor-made anatase TiO2 nanoparticles and monodisperse PS microspheres showed a high degree of dispersion stability under basic conditions. Hydrothermal treatment of the TiO2 dispersion favored the crystallinity of the coated film and provided small volume contraction after thermal calcinations. The high degree of dispersion stability enabled to increase TiO2 content in a binary mixture, which is more favorable toward the robust and large-area IO film. The calcined films exhibited excellent mechanical robustness and intimate interfacial contact with the glass substrate. which in turn resulted in higher TiO2 content near the glass substrate. The TiO2 IO film was tested as a dye-sensitized solar cell (DSSC) photoelectrode, and a single cell showed a relatively high photon-to-current conversion efficiency of 4.2%. The high TiO2 content of IO film and its good adhesion to the FTO subratrate remarkably improved in the performance of the solar cell compared to the previous investigations where post-infiltration of TiO2 had been employed.
Keywords: PHOTONIC CRYSTALS; TITANIUM-DIOXIDE; THIN-FILMS; TEMPLATES; COLLOIDS; ANATASE; CELLS